(untitled) - Chafe, William Henry (Oxford, 1999)
This book chronicles America's roller-coaster journey through the decades since World War II. It portrays the significant cultural and politic themes which have colored American country's past and present, including issues of race, class, gender, foreign policy, and economic and social reform. The book examines such subjects as the Vietnam War, the civil rights movement, the origins and the end of the Col War, the culture of the 1970s, the Reagan years, and the Perot phenomenon and the rise of the independent third party as a major force in presidential politics ...
Keywords: United states,United states,United states; Politics and government,Politics and government,Social conditions; 1945-1989,1989-,1945-